Photoluminescent properties of Ca2RE8（SiO4）6O2：A （RE=Y, Gd; A=Pb^2＋, Mn^2＋） phosphor films prepared by sol-gel process - 韩秀梅 林君 李哲 齐西伟 李明亚 王晓强 (Journal of rare earths, 2008)
Ca2RE8（SiO4）6O2：A （RE=Y, Gd; A=Pb^2＋, Mn^2＋） phosphor fdms were dip-coated on quartz glass substmtes through the sol-gel process. X-ray diffraction （XRD）, photoluminescence （PL） spectra as well as lifetimes were used to characterize the resulting films. Under short wavelength UV excitation, the film showed a red emission with medium intensity. The decay curve of Mn^2＋ luminescence in Ca2Gd8（SiO4）6O2：Pb Mn film could be fitted into a single exponential function. The lifetime of Mn^2＋ was 10.21 ms in Ca2Gd8（SiO4）6O2.